2008
DOI: 10.1159/000121359
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging of Rectal Tumors: Comparison of Endorectal Ultrasound, Hydro-CT, and High-Resolution Endorectal MRI

Abstract: Aim: The aim of this study was to compare transrectal ultra-sound (TRUS), hydro-computed tomography (hydro-CT), and endorectal magnetic resonance imaging (MRI) in the preoperative staging of rectal cancer. Patients and Methods: 23 patients with rectal adenocarcinoma underwent TRUS, hydro-CT, and MRI (1 Tesla) with endorectal coil. The results were correlated with the histopathological findings based on the TNM classification. Results: T staging with TRUS, hydro-CT, and endorectal MRI correlated with the histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…These findings were quite in line with a study conducted by Dinter et al [27], which reported overstaging by Hydro-CT in 3/23 (13%) patients. However, low accuracy in detecting T1/2 lesions and nodal staging posed significant restrictions [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings were quite in line with a study conducted by Dinter et al [27], which reported overstaging by Hydro-CT in 3/23 (13%) patients. However, low accuracy in detecting T1/2 lesions and nodal staging posed significant restrictions [27].…”
Section: Discussionsupporting
confidence: 93%
“…These findings were quite in line with a study conducted by Dinter et al [27], which reported overstaging by Hydro-CT in 3/23 (13%) patients. However, low accuracy in detecting T1/2 lesions and nodal staging posed significant restrictions [27]. More recent studies reported accuracies of up to 87% for T staging and 80% for N staging by MDCT with multiplanar reconstruction [7,28,29].…”
Section: Discussionsupporting
confidence: 93%
“…Recent data suggest that EUS staging of rectal cancer after RT-CT is inaccurate [1] , while MRI seems to be costeffective in selecting appropriate patients for neoadjuvant therapy and its use is justified for local staging. After RT-CT, EUS and MRI might be useful to demonstrate tumor shrinkage and down-staging in responsive tumors, which might occasionally disappear completely [17,18,[20][21][22][23] . Increasing reflectivity and signal changes indicate fibrosis, but unless significant tumor bulk remains, neither modality seems to be able to exclude the persistence of tumor cells within fibrosis [24][25][26][27][28] .…”
Section: Mezzi G Et Al Eus and Mri In Rectal Cancermentioning
confidence: 99%
“…38 Although rigid endoscopic rectal US effectively predicts levator ani muscle or external anal sphincter invasion, it does not have the ability to adequately evaluate more proximal tumors, regions beyond the field of TME or the facility to sample lymph nodes under real-time guidance. [39][40][41][42][43] Nodal metastasis is an independent poor prognostic indicator in patients with rectal cancer. It would appear that individuals with EMLNM may be a distinct subgroup at increased risk of local recurrence and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%